Aberrant spontaneous static and dynamic amplitude of low‐frequency fluctuations in cerebral small vessel disease with or without mild cognitive impairment - Zhang, Xulian; Wang, Zhigang; Zheng, Darui; Cao, Xuan; Qi, Wenzhang; Yuan, Qianqian; Zhang, Da; Liang, Xuhong; Ruan, Yiming; Zhang, Shaojun; Tang, Weijie; Huang, Qingling; et al. (Brain and behavior, 2023)
Background Cerebral small vessel disease (CSVD) is considered an age‐related degenerative neurological disorder and the most common risk factor for vascular cognitive impairment (VCI). The amplitude of fluctuation of low frequency (ALFF) can detect altered intrinsic brain activity in CSVD. This study explored the static and dynamic ALFFs in the early stage of CSVD with (CSVD‐M) or without (CSVD‐W) mild cognitive impairment (MCI) in these patients and how these changes contribute to cognitive deterioration. Methods Thirty consecutive CSVD cases and 18 healthy controls (HC) were included in this study. All the participants underwent a 3D magnetization‐prepared rapid gradient‐echo (MPRAGE) sequence to obtain structural T1‐weighted images. Simultaneous multislice imaging 5(SMS5) was used for resting‐state functional MRI (rs‐fMRI), and Data Processing and Analysis of Brain Imaging software helped determine static ALFF (sALFF). The dynamic ALFF (dALFF) was calculated using the sliding window method of DynamicBC software. Analysis of Covariance (ANCOVA) and two‐sample t‐test were used to evaluate the sALFF and temporal variability of dALFF among the three groups. The subjects were rated on a broad standard neuropsychological scale. Partial correlation analysis was used to evaluate the correlation between sALFF and dALFF variability and cognition (Bonferroni correction, statistical threshold set at p < .05). Results Compared with HCs, the CSVD‐M group indicated decreased sALFF values in the bilateral cerebellum posterior lobe (CPL) and the left inferior Parietal Lobule (IPL), with increased sALFF values in the right SFG. For dALFF analysis, the CSVD‐W group had significant dALFF variability in the right fusiform gyrus compared with HC. Moreover, the postcentral gyrus (PoCG) was significantly high in the CSVD‐W group. While in the CSVD‐M group, the bilateral paracentral lobules (PL) revealed significantly elevated dALFF variability and low dALFF variability in the left CPL and right IPL compared with HCs. The CSVD‐M group had high dALFF variability in the bilateral PL but low dALFF variability in the left middle temporal gyrus (MTG) and right PoCG compared with the CSVD‐W group. The partial correlation analysis indicated that dALFF variability in the left MTG was positively associated with EM (r = 0.713, p = .002) in CSVD‐W and CSVD‐M groups. In the groups with CSVD‐M and HC, altered dALFF variability in the bilateral PL was negatively correlated with EM (r = −0.560, p = .002). Conclusion There were significant changes in sALFF and dALFF variability in CSVD patients. Abnormal spontaneous static and dynamic ALFFs may provide new insights into cognitive dysfunction in CSVD with MCI and may be valuable biomarkers for early diagnosis.